(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
In recent years, the number of drugs of biotechnological origin available for many different diseases has increased exponentially, including different types of cancer, diabetes mellitus, infectious diseases (e.g. AIDS Virus / HIV) as well as cardiovascular, neurological, respiratory, and autoimmune diseases, among others. The pharmaceutical industry has used different technologies to obtain new and promising active ingredients, as exemplified by the fermentation technique, recombinant DNA technique and the hybridoma technique. The expiry of the patents of the first drugs of biotechnological origin and the consequent emergence of biosimilar products, have posed various questions to health authorities worldwide regarding the definition, framework, and requirements for authorization to market such products.